Objective Olfactory Outcomes after Revision Endoscopic Sinus Surgery. Issue 4 (July 2013) - Hsu, Chao-Yuan; Wang, Ying-Piao; Shen, Ping-Hung; Weitzel, Erik Kent; Lai, Jen-Tsung; Wormald, Peter-John
Background: Patients who suffer from hyposmia and anosmia report a negative effect on their overall quality of life. Smell disturbance of patients with chronic rhinosinusitis (CRS) can improve after endoscopic sinus surgery (ESS). Although several studies have shown that 50–83% of patients may notice an improvement in olfactory function after ESS, the olfactory improvement after revision ESS (RESS), especially by objective measurements, is still lacking. Methods: Olfactory function was assessed by the traditional Chinese version of the University of Pennsylvania Smell Identification Test (UPSIT-TC) preoperatively and postoperatively, recorded as smell identification test (SIT) score. Olfactory outcomes from anosmia to hyposmia/normosmia, or from hyposmia to normosmia, were considered as "improvement." Postoperative assessments were divided into two periods: period 1 (P1) is defined as >6 but <12 months postoperatively; period 2 (P2) is defined as >12 but <24 months postoperatively. Results: Thirty-two patients with smell disturbance preoperatively (period 0 [P0]) and confirmed by UPSIT-TC were enrolled into this study. Mean SIT score at P0 was 13.3; mean SIT score at P1 was 18.6; mean SIT score at P2 was 20.4. The presence of nasal polyps blocking the olfactory cleft were associated with better olfaction improvements (p < 0.05) as was the degree of mucosal swelling. The overall improvement rates were 44.8 and 47.8% at P1 and P2, respectively. Conclusion: RESS resulted in objective evidence of olfactory improvement in approximately one-half of our cohort over 16 months of follow-up and offers a treatment option for an otherwise poor prognosis condition.